2017
DOI: 10.1136/oemed-2016-104207
|View full text |Cite
|
Sign up to set email alerts
|

Military small arms fire in association with acute decrements in lung function

Abstract: Exposure to fumes from military weapons might be a respiratory hazard for soldiers who do live-fire training regularly or are in a closed combat environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…Our finding that gunshot smoke particles emitted from pistols in the breathing zone of the shooter resemble particles emitted during welding, corroborating previous findings (Antonini, 2003;Grabinski et al, 2017;Wingfors et al, 2014). Military soldiers that inhaled gunshot smoke particle fumes from Pb-free military small arms ammunitio (dominated by oxides of Mn, Fe, Cu, and Zn) developed neutrophilic inflammation within 24 h in both upper airways and blood circulation, along with reduced lung function and impaired alveolar-vascular barrier integrity (Borander et al, 2017;Sikkeland et al, 2018;Voie et al, 2014). proteins in plasma than Pb-containing ammunition (Borander et al, 2017;Sikkeland et al, 2018).…”
Section: Particle-induced Effects On Primary Endothelial Huvec Cellssupporting
confidence: 90%
See 2 more Smart Citations
“…Our finding that gunshot smoke particles emitted from pistols in the breathing zone of the shooter resemble particles emitted during welding, corroborating previous findings (Antonini, 2003;Grabinski et al, 2017;Wingfors et al, 2014). Military soldiers that inhaled gunshot smoke particle fumes from Pb-free military small arms ammunitio (dominated by oxides of Mn, Fe, Cu, and Zn) developed neutrophilic inflammation within 24 h in both upper airways and blood circulation, along with reduced lung function and impaired alveolar-vascular barrier integrity (Borander et al, 2017;Sikkeland et al, 2018;Voie et al, 2014). proteins in plasma than Pb-containing ammunition (Borander et al, 2017;Sikkeland et al, 2018).…”
Section: Particle-induced Effects On Primary Endothelial Huvec Cellssupporting
confidence: 90%
“…Military soldiers that inhaled gunshot smoke particle fumes from Pb-free military small arms ammunitio (dominated by oxides of Mn, Fe, Cu, and Zn) developed neutrophilic inflammation within 24 h in both upper airways and blood circulation, along with reduced lung function and impaired alveolar-vascular barrier integrity (Borander et al, 2017;Sikkeland et al, 2018;Voie et al, 2014). proteins in plasma than Pb-containing ammunition (Borander et al, 2017;Sikkeland et al, 2018). Furthermore, gunshot smoke particles from small arms decreased cell viability and induced oxidative stress and immune activation in exposed alveolar epithelial (A549) cells, and these toxic responses significantly correlated with the Cu and Zn content in the samples (Bergström et al, 2015).…”
Section: Particle-induced Effects On Primary Endothelial Huvec Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a comparison of harder steel core ammunition, which results in larger abrasion of the bullet and more metal fragments in the smoke, to Pb core ammunition, the steel core produced more Cu and Zn than the Pb core ammunition when fired in the same rifle. This suggests that exposure to metals from firing ammunition is more affected by barrel design than bullet type 20 . It has been reported that smoke particle sizes (a major peak at 1-4 µm) were largely unchanged from firing different ammunitions 10,18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…R175H, R248G -fs*-mutation type: insertion-frameshift; *-mutation type: nonsense mutation; the protein coding sequence ends at a translation termination codon (stop codon); del-mutation type: deletion; ins-mutation type: insertion & Koch), soldiers got flu-like symptoms. Further investigations have revealed that exposure to gunshot fumes may induce health effects such as fever, coughing, inflammations reactions, and reduced lung capacity (Voie et al 2014, Borander et al 2017. Moreover, the high levels of carbon monoxide in the fume lead to increased levels of carboxyhemoglobin in the blood.…”
Section: Discussionmentioning
confidence: 99%